Ranges of Backwater Curves in Lower Odra = Zasięgi krzywej spiętrzenia dolnej Odry - Mańko, Robert (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the paper, the backwater curve ranges at the mouth of the Odra River with changing boundary conditions were analysed. The aim of the study is to determine which boundary condition, i.e. stage of lower cross-section or flow in upper cross-section, has a greater impact on the formation of the backwater curve at the mouth of the Odra River.
Keywords: backwater curves; steady flow; mouth of the Odra River; Bernoulli equation; krzywe spiętrzenia; ruch ustalony jednostajny; ujście Odry; równanie Bernoulliego